PENGUKURAN KINERJA SUPPLY CHAIN DENGAN MODEL SUPPLY CHAIN OPERATION REFERENCE (SCOR) DAN ANALYTHICAL HIERARCHY PROCESS (AHP) PADA CV. ANNET SOFA - Edit Rusnita (Universitas Muhammadiyah Sorong, 2023)
One of the company's strategies to survive and excel in industry competition is to improve supply chain performance. These improvements can be made by measuring the supply chain. The results can be used as feedback which provides information about the condition of supply chain implementation and the point where the company needs to adjustments and improvements company's supply chain so that can improve service to consumers and company revenue. Measurement of supply chain performance is carried out using the Supply chain Operation Reference (SCOR) and Analythical Hierarchy Process (AHP) models. SCOR is a process reference model for supply chain operations which is divided into five basic supply chain management processes, plan, source, make, deliver, and return. In using AHP, the weights for each metric at level 1 to work metrics are obtained. In this study, measurements were taken at CV Annet Sofa. The results show that the value of overall performance CV.Annet Sofa supply chain is 74.31769 which indicates that the performance of the supply chain is good. As for the 28 performance metrics that were measured, there were 7 metrics that had not reached the target because they obtained a performance value of <60, so evaluation and improvement needed to be carried out.